FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU IBU RUMAH TANGGA NELAYAN DALAM MENGGUNAKAN MEDIA MASSA SEBAGAI SUMBER INFORMASI - Yuliarso, M. Zulkarnain (Jurnal AGRISEP, 2009)
The research was aimed to 1) to research house wife’s behavior in using mass media as information,   2) study of  factors that related to house wife’s behavior in using mass media. The data were collected in August 2009 at Pondok Besi dan Berkas. Sample number in this research were 40 people was taken by simple random method.  In explaining the first purposes were use the descriptive analysis, and the second purpose was analyzed with Spearman Rank correlation test. The information which was gained from mass media especially the things related to entertainment, health, and religion could be helpful for daily life both for their personal and social life. The result of statistical analysis showed that the formal education, number of working hour, household income, their perception on information and attitude to living change, were apparently related to using mass media.